Fatty Acid Metabolism and T Cells in Multiple Sclerosis - Pompura, Saige L.; Hafler, David A.; Dominguez-Villar, Margarita (Frontiers in Immunology, 2022)
Cellular metabolic remodeling is intrinsically linked to the development, activation, differentiation, function, and survival of T cells. T cells transition from a catabolic, naïve state to an anabolic effector state upon T cell activation. Subsequently, specialization of T cells into T helper (Th) subsets, including regulatory T cells (Treg), requires fine-tuning of metabolic programs that better support and optimize T cell functions for that particular environment. Increasingly, studies have shown that changes in nutrient availability at both the cellular and organismal level during disease states can alter T cell function, highlighting the importance of better characterizing metabolic-immune axes in both physiological and disease settings. In support of these data, a growing body of evidence is emerging that shows specific lipid species are capable of altering the inflammatory functional phenotypes of T cells. In this review we summarize the metabolic programs shown to support naïve and effector T cells, and those driving Th subsets. We then discuss changes to lipid profiles in patients with multiple sclerosis, and focus on how the presence of specific lipid species can alter cellular metabolism and function of T cells.